A lab-made screen-printed sensing strip for sensitive and selective electrochemical detection of butylated hydroxyanisole. Issue 6 (8th February 2023) - Bas, Salih Zeki; Cetiner, Rumeysa; Teke, Deniz; Ozmen, Mustafa
Abstract : This study describes the fabrication of a lab-made screen-printed electrode (LabSPE) and its sensing ability for the detection of butylated hydroxyanisole (BHA) which is a synthetic antioxidant utilized widely in food industries. Abstract : This study describes the fabrication of a lab-made screen-printed electrode (LabSPE) and its sensing ability for the detection of butylated hydroxyanisole (BHA) which is a synthetic antioxidant utilized widely in food industries. The lab-made screen-printed electrodes were printed on a polycarbonate substrate stepwise via a screen-printing technique using various inks suitable for electrode templates and then modified for the detection of BHA. As for the design of the sensor, firstly, graphitic carbon nitride (g-C3 N4 ) was synthesized electrochemically through the one-pot synthesis method. After the synthesis of Fe3 O4 nanoparticles (Fe3 O4 NPs), the surface of SPE was modified with the dual composite consisting of g-C3 N4 and Fe3 O4 NPs. Lastly, platinum nanoparticles (Pt NPs) were deposited electrochemically on the modified electrode in 0.5 M HCl solution containing 2 mM H2 PtCl6 at a constant potential of 0.25 V for 45 s. After optimization of varied parameters such as pH of the electrolyte solution, deposition time, and deposition potential, the current responses of the sensor (Pt/g-C3 N4 –Fe3 O4 /LabSPE) toward BHA displayed linearity in the wide concentration range of 0.25 μM to 90 μM with a low detection limit of 0.053 μM. The selectivity of Pt/g-C3 N4 –Fe3 O4 /SPE was tested successfully in the presence of other antioxidants (BHT, TBHQ, GA, and PG). Moreover, the applicability of the proposed sensor for practical tests was verified by the detection of BHA in commercial samples.